POSSIBILITIY OF SHORT-TERM STRESS INFLUENCES IMPLEMENTATION IN BIOLOGICALLY ACTIVE COMPOUNDS SCREENING - A. S. Tarasov; E. I. Morkovin; V. V. Stepanova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
This work presents the analysis of phobic anxiety behavioral reactions connected with short-term stress influences. We have established that 15 minutes forced swimming reduces locomotory and exploratory activity of animals without any connection with physical exhaustion. Short-term isolation provokes the increase of irrational searching activity connected with spatial disorder and agitation. During this work we have formed an algorithm which allowed fast screening of anxio-lytics and antidepressants